Perancangan Sistem Penerbitan dan Verifikasi E-Ijazah dan E-Transkrip Menggunakan Teknologi Blockchain pada Universitas Dinamika Bangsa - Toscany, Afrizal; Bustasmi, M.Irwan; Saputra, Chindra (The Indonesian Journal of Computer Science, 2022)
With the development of increasingly sophisticated technology, the act of counterfeiting becomes an easy thing to do. An image editor application intended to heed a work of art, has now turned its function into a tool for document forgery.  Forgery of a diploma is a form of deviant behavior that violates the rule of law and makes the perpetrator criminal. Economic conditions, low education and the need to get a job are reasons for perpetrators to commit forgery. In addition, political motives are also often a reason to get political office.  One of the technologies to anticipate this problem is to apply blockcerts to electronic diplomas. Blockcert is built using blockchain technology that provides transparency and accountability in the storage of certificates and diplomas. This research resulted in a system of publishing and validating e-diplomas and e-transcripts at the University of Dinamika Bangsa which are stored on a private blockchain. The system has been tested and all modules are running properly according to the expected output.